2010
DOI: 10.1111/j.1438-8677.2010.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of sucrose phosphate synthase (SPS) and sucrose synthase (SS) in sugarcane (Saccharum) cultivars

Abstract: Sucrose phosphate synthase (SPS; EC 2.4.1.14) and sucrose synthase (SS; EC 2.4.1.13) are key enzymes in the synthesis and breakdown of sucrose in sugarcane. The activities of internodal SPS and SS, as well as transcript expression were determined using semi-quantitative RT-PCR at different developmental stages of high and low sucrose accumulating sugarcane cultivars. SPS activity and transcript expression was higher in mature internodes compared with immature internodes in all the studied cultivars. However, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 45 publications
8
66
4
2
Order By: Relevance
“…However, the mechanism of how SCMV infection affects SPS protein biosynthesis remains unclear. Since SPS plays a crucial role in sucrose biosynthesis, incorporating with Sucrose Phosphate Phosphatase (SPP) [38,39], the increased activity of SPS would result in a higher sucrose accumulation [40]. In contrast, our result showed a lower SPS activity, but higher sucrose accumulation in infected leaves (Figure 4b).…”
Section: Discussioncontrasting
confidence: 55%
“…However, the mechanism of how SCMV infection affects SPS protein biosynthesis remains unclear. Since SPS plays a crucial role in sucrose biosynthesis, incorporating with Sucrose Phosphate Phosphatase (SPP) [38,39], the increased activity of SPS would result in a higher sucrose accumulation [40]. In contrast, our result showed a lower SPS activity, but higher sucrose accumulation in infected leaves (Figure 4b).…”
Section: Discussioncontrasting
confidence: 55%
“…Expression analysis of SAI gene by RT-PCR Expression analysis of SAI gene was performed by following the method as described by Verma et al (2010) for Sucrose phosphate synthase and sucrose synthase genes in sugarcane. Total RNA was isolated from the mature and immature internodes of the different cultivars and cDNAs were synthesized as described above.…”
Section: Extraction and Estimation Of Endogenous Free Sugarsmentioning
confidence: 99%
“…RNA isolation and cDNA synthesis RNA isolation and cDNA synthesis was performed as described by Verma et al (2010) for sugarcane. Total RNA was isolated from 100 mg of plant samples (mature and immature internodes) using total RNA isolation kit (Sigma).…”
Section: Extraction and Estimation Of Endogenous Free Sugarsmentioning
confidence: 99%
“…Pan et al (2007) reported that four enzymes made great contribution to sucrose accumulation in sugarcane internodes, and SAI, SS and NI were negatively while SPS was positively correlated with sucrose content in cane, respectively. Verma et al (2011) emphasized that SPS activity was positively correlated with sucrose content and negatively correlated with hexose sugars content, but SS activity was negatively correlated with sucrose content and positively correlated with hexose sugars content. Changes of sugar contents due to exogenous ethylene treatment were supported by the changes of different sugar metabolizing enzymes.…”
Section: Enzymes In Carbohydrate Metabolismmentioning
confidence: 99%